WHY DO STUDENTS ENGAGE IN BULLYING? OTHER FACTORS FOUND TO CONTRIBUTE TO STUDENT BULLYING - Alwi, Nur Azmi; Dona, Three Rahmadona; Nasution, Dina Erina; Lestari, Elza Eka (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
Bullying is a significant issue in the Indonesian education system, and one way to address it is by identifying its causes. This research aims to analyze the reasons behind students engaging in bullying. The study employs a qualitative approach using a descriptive method involving interviews, observations, and documentation to uncover the factors contributing to student bullying. The subjects of this research were five students from class IIA, selected through purposive sampling. Data obtained were analyzed using triangulation techniques. The research results indicate that the factors contributing to students' bullying behavior in elementary school include: 1) Family factors, as parenting styles and home conditions can influence a child's behavior; 2) Peer environment factors, such as the attitudes and characteristics of peers who exert a dominant influence, as students at this age are easily influenced by others; and 3) Factors related to the bullying victims themselves, as their daily attitudes affect how they are treated by others. Based on the research findings, these three factors can be the focus of efforts to prevent and address bullying cases in educational environments, thereby reducing bullying incidents in schools.